(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Wiyono Village, Gedong Tataan District, Pesawaran Regency, has significant agricultural potential, including nutmeg. Often, underutilized nutmeg shell waste can become a source of environmental pollution. This community service program aims to empower members of the Mentari Women’s Farmers Group (KWT) through training in the production of biobriquettes from nutmeg waste as a clean and affordable alternative fuel, while simultaneously increasing the participants’ economic independence. The program involved 20 KWT members, using theory, hands-on practice, and independent mentoring, with support from lecturers from various study programs and two students. Pre-test and post-test evaluations showed an increase in participants’ ability to produce biobriquettes from 50% to 90%. The training results fostered participant enthusiasm, strengthened technical and social capacity, reduced organic waste, and opened up new business opportunities. This program aligns with the principles of sustainable development (SDGs), particularly those related to clean energy, decent work, and inclusive economic growth. This activity can be used as a model for community empowerment based on agricultural waste management.